Prevalence of end‐of‐life visual impairment in patients followed for glaucoma. (19th December 2012) - Ernest, Paul J. G.; Busch, Michiel J. W. M.; Webers, Carroll A. B.; Beckers, Henny J. M.; Hendrikse, Fred; Prins, Martin H.; Schouten, Jan S. A. G.
Abstract. Purpose: To assess the prevalence of end‐of‐life visual impairment in patients followed for glaucoma. Methods: Data of 122 patients followed for glaucoma who had died between July 2008 and July 2010 and who had visited the ophthalmology outpatient department of a large non‐academic Dutch hospital were collected from the medical files. Sixty‐one patients had open‐angle glaucoma (OAG), and 61 patients were suspect for glaucoma or had ocular hypertension (OHT). Visual impairment was defined as a mean deviation value <−15 dB or a Snellen visual acuity <0.3 (20/60) of the better eye. We determined the number of patients with visual impairment on the last patient visit before death and investigated its main explanations. Results: Overall, the mean age at death was 81.8 years after a mean follow‐up period of 9.2 years. Seventy‐three per cent of all patients had their last visit in the year preceding death. In OAG, 16 patients (26%) had an end‐of‐life visual impairment. In nine patients (15%), this was caused by glaucoma. Eight of them had substantial visual loss at the initial visit. Six (10%) impaired OAG cases were mainly explained by ocular comorbidity, and there was an equal contribution of comorbidity and glaucoma in one case. Five glaucoma suspects or patients with OHT (8%) were visually impaired at death and these were all caused by ocular comorbidity. Conclusion: The prevalence of end‐of‐life visual impairment is considerable in patients with OAG. Substantial visual loss at baseline is an important contributing factor. In glaucoma suspects or patients with OHT, the prevalence is lower and can be attributed to ocular comorbidity.